Practical considerations for assignment of photon numbers with SNSPDs - Schapeler, Timon; Mischke, Isabell; Schlue, Fabian; Stefszky, Michael; Brecht, Benjamin; Silberhorn, Christine; Bartley, Tim (APL Quantum)
Superconducting nanowire single-photon detectors (SNSPDs) can enable photon-number resolution (PNR) based on accurate measurements of the detector’s response time to few-photon optical pulses. In this work, we investigate the impact of the optical pulse shape and duration on the accuracy of this method. We find that Gaussian temporal pulse shapes yield cleaner arrival-time histograms and, thus, more accurate PNR, compared to bandpass-filtered pulses of equal bandwidth. For low system jitter and an optical pulse duration comparable to the other jitter contributions, photon numbers can be discriminated in our system with a commercial SNSPD. At 60 ps optical pulse duration, photon-number discrimination is significantly reduced. Furthermore, we highlight the importance of using the correct arrival-time histogram model when analyzing photon-number assignment. Using exponentially modified Gaussian distributions, instead of the commonly used Gaussian distributions, we can more accurately determine photon-number misidentification probabilities. Finally, we reconstruct the positive operator-valued measures of the detector, revealing sharp features that indicate the intrinsic PNR capabilities.

Bridging chemistry and Gaussian boson sampling: a photonic hierarchy of approximations for molecular vibronic spectra - Eickmann, Jan-Lucas; Luo, Kai-Hong; Roiz, Mikhail; Lammers, Jonas; Atzeni, Simone; Pandey, Cheeranjiv; Lütkewitte, Florian; Shirazi, Reza G.; Schlue, Fabian; Brecht, Benjamin; Rybkin, Vladimir V.; Stefszky, Michael; et al. (npj Quantum Information)
Simulating vibronic spectra is a central task in physical chemistry, offering insight into important properties of molecules. Recently, it has been experimentally demonstrated that photonic platforms based on Gaussian boson sampling (GBS) are capable of performing these simulations. However, whether an actual GBS approach is required depends on the molecule under investigation. To develop a better understanding on the requirements for simulating vibronic spectra, we explore connections between theoretical approximations in physical chemistry and their photonic counterparts. Mapping these approximations into photonics, we show that for certain molecules the GBS approach is unnecessary. We place special emphasis on the linear coupling approximation, which in photonics corresponds to sampling from multiple coherent states. By implementing this approach in experiments, we demonstrate improved similarities over previously reported GBS results for formic acid and identify the particular attributes that a molecule must exhibit for this, and other approximations, to be valid. These results highlight the importance in forming deeper connections between traditional methods and photonic approaches.

Optimizing photon-number resolution with superconducting nanowire multi-photon detectors - Schapeler, Timon; Schlue, Fabian; Stefszky, Michael; Brecht, Benjamin; Silberhorn, Christine; Bartley, Tim (Advanced Photon Counting Techniques XIX)

Jitter in photon-number-resolved detection by superconducting nanowires - Sidorova, Mariia; Schapeler, Timon; Semenov, Alexej D.; Schlue, Fabian; Stefszky, Michael; Brecht, Benjamin; Silberhorn, Christine; Bartley, Tim (APL Photonics)
By analyzing the physics of multi-photon absorption in superconducting nanowire single-photon detectors (SNSPDs), we identify physical components of jitter. From this, we formulate a quantitative physical model of the multi-photon detector response that combines the local detection mechanism and local fluctuations (hotspot formation and intrinsic jitter) with the thermoelectric dynamics of resistive domains. Our model provides an excellent description of the arrival-time histogram of a commercial SNSPD across several orders of magnitude, both in arrival-time probability and across mean photon number. This is achieved with just three fitting parameters: the scaling of the mean arrival time of voltage response pulses, as well as the Gaussian and exponential jitter components. Our findings have important implications for photon-number-resolving detector design, as well as applications requiring low jitter, such as light detection and ranging (LIDAR).
Keywords: Jitter; PNR; SNSPD

Electrical trace analysis of superconducting nanowire photon-number-resolving detectors - Schapeler, Timon; Lamberty, Niklas; Hummel, Thomas; Schlue, Fabian; Stefszky, Michael; Brecht, Benjamin; Silberhorn, Christine; Bartley, Tim (Physical Review Applied)
We apply principal component analysis (PCA) to a set of electrical output signals from a commercially available superconducting nanowire single-photon detector (SNSPD) to investigate their photon-number-resolving capability. We find that the rising edge as well as the amplitude of the electrical signal have the most dependence on photon number. Accurately measuring the rising edge while simultaneously measuring the voltage of the pulse amplitude maximizes the photon-number resolution of SNSPDs. Using an optimal basis of principal components, we show unambiguous discrimination between one- and two-photon events, as well as partial resolution up to five photons. This expands the use case of SNSPDs to photon-counting experiments, without the need of detector multiplexing architectures. Published by the American Physical Society 2024

Experimental retrieval of photon statistics from click detection - Krishnaswamy, Suchitra; Schlue, Fabian; Ares, L.; Dyachuk, V.; Stefszky, Michael; Brecht, Benjamin; Silberhorn, Christine; Sperling, Jan (Physical Review A)